EFFECTS OF STREET TRADING ON URBAN AREAS IN NIGERIA - Gani, Bogoro Audu (IJRDO - Journal of Applied Management Science, 2015)
Street trading is a form of squatting that involves perpetual movement that may occur within established market places or around road intersections which results to several negative impacts on physical environment such as traffic congestion, environmental pollution, and aesthetically unpleasing environment. This study looks at the effects on cities in Nigeria. Three urban areas Bauchi, Lagos and Port Harcourt were sampled to study the impact of street trading in Nigerian urban areas. 100 questionnaires were administered to each of the three urban centers selected. It is found that 40.59% of streets traders are migrants from the rural areas The study discovered that most of the streets traders indiscriminately disposed of their refuse by burning and dumping in the drainage there by blocking the drainage channels causing flood during rainy season and 24.75% dumped their waste right on the roadside. There is disorderliness in the arrangement of different methods used in displaying of items by street traders there by making the study area appear as an insightful and unpleasant urban environment thus displeasing visual effect and 28.71% of streets traders encroached into the road with up to 1-1.5m and above causing serious traffic problem. The paper recommends development of rural areas to reduce rural-urban migration, relocating those that encroached to in the road, and the provision of moveable refuse collection points